PENGARUH PROGRAM TAX AMNESTY, SANKSI PAJAK, DAN KUALITAS PELAYANAN FISKUS TERHADAP KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI - Muhroni Muhroni (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study was to describe (1) the influence of tax amnesty variable to the variable of willingness to pay the tax, (2) the influence of tax sanction variable to the variable of taxpayer willingness, (3) the influence of the taxi waiter variable variable to taxpayer willingness variable, (4) from the variable tax amnesty, tax sanction, and the quality of tax service to the variable of willingness to pay taxes together. This research belongs to research type exspos facto. The population is an individual taxpayer who is in the area of Yogyakarta as well as used as a sample of research. Data collection methods used questionnaires, while data analysis techniques used multiple regression analysis supported by F (F - Test) and T (T-Test) test and classical assumption test consisting of multicollinearity test, normality test, heterokedasticity test. The results showed that the linear multiple regression equation for four predictors is Y = 2.917 + 0.366X1 + 0.212X2 + 0.208X3 That is, tax amnesty (x1), tax penalty (X2), and fiscal service quality (X3) tax. The magnitude of influence seen from the coefficient of determination (R2). The value of coefficient of determination (R2) through regression analysis of 0.459. The result of coefficient of determination showed that tax amnesty, tax sanction, and service quality of fiskus give positive influence to the willingness of paying tax equal to 45,9% and the rest equal to 54,1% influenced by other factor.